2020
DOI: 10.1200/jco.2020.38.15_suppl.7000
|View full text |Cite
|
Sign up to set email alerts
|

The oncology hospital at home: Health care utilization outcomes from the huntsman at home trial.

Abstract: 7000 Background: Unplanned hospitalizations and emergency department (ED) visits are common during cancer care. Providing acute hospital level care at home may add value by decreasing hospital and ED use. We conducted the first evaluation of an oncology Hospital-at-Home program, Huntsman at Home (H@H). Methods: The Huntsman Cancer Institute began H@H services in 2018 and accepts referral of cancer patients for acute-medical or post-surgical care at home. Patients are admitted who require continued acute level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In PrefHer, 60.4% of patients would hypothetically have preferred SC home administration [13]. This concept of flexible care is being investigated in an 'oncology hospital-at-home program' in the US, which reported fewer hospitalisations and emergency department visits and reduced costs versus standard processes [15]. Chemotherapy at home is a well-embedded UK practice.…”
Section: Discussionmentioning
confidence: 99%
“…In PrefHer, 60.4% of patients would hypothetically have preferred SC home administration [13]. This concept of flexible care is being investigated in an 'oncology hospital-at-home program' in the US, which reported fewer hospitalisations and emergency department visits and reduced costs versus standard processes [15]. Chemotherapy at home is a well-embedded UK practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent trial found decreased cost and healthcare use among patients with cancer hospitalized at home. 54 , 55 Studies published 2 decades ago demonstrated that patients with neutropenic fever may be treated at home with antibiotics and close monitoring and thus may be great candidates for home hospitalization. 56 Furthermore, other illnesses may be amenable to home hospital care by further exploring the literature and innovating care protocols.…”
Section: What Is Home Hospital?mentioning
confidence: 99%
“…We need to invest in research to better understand other conditions that may benefit from home hospital. For example, a recent trial found decreased cost and healthcare use among patients with cancer hospitalized at home 54,55 . Studies published 2 decades ago demonstrated that patients with neutropenic fever may be treated at home with antibiotics and close monitoring and thus may be great candidates for home hospitalization 56 .…”
Section: What Is Home Hospital?mentioning
confidence: 99%
“…H@H reports reduced hospitalizations, ED visits, and total costs among patients who participate in the program. 7 Concerns about safety, feasibility, patient-centeredness, and reimbursement exist for cancer hospital-at-home programs as well. Despite these concerns, however, hospital-at-home models exist and are expanding.…”
Section: Acute Carementioning
confidence: 99%